Value of Cranial Ultrasonography and Resistive Index of Cerebral Arteries in Predicting Neuromotor Outcomes in Newborns with Hypoxic Ischaemic Encephalopathy - Shamrendra Narayan; Pratish K Singh; Nilotpal Choudhury; Rakesh Bhatia; Dipti Agarwal; Vandana Verma Ahluwalia (JCDR Research and Publications Pvt. Ltd., 2018)
Introduction: Perinatal asphyxia is one of the leading cause of neonatal mortality and childhood morbidity. Use of cranial Ultrasonography (USG) and cranial arterial doppler indices has been evaluated for predicting risk of neuromotor impairment. Aim: Study was aimed to evaluate the role of cranial USG and Resistive Index (RI) of Anterior and Middle Cerebral Arteries (ACA, MCA) in predicting neuromotor outcomes at six months of age in term neonates with perinatal asphyxia and Hypoxic Ischaemic Encephalopathy (HIE). Materials and Methods: This prospective study was carried out at a tertiary care teaching hospital. Subjects with perinatal asphyxia and HIE were grouped in different Sarnat and Sarnat stages. Cranial USG and RI measurement of ACA, MCA was done within five days of birth. They were followed up at six months of age for neuromotor outcome. Outcome was correlated with Sarnat stages, USG finding and RI of ACA, MCA. It was carried out using R statistical environment. Results: A total of 43 neonates with perinatal asphyxia and HIE were evaluated for neuromotor outcomes. Both ACA and MCA, RI were also significantly associated with the clinical stages (p<0.0001). Out of these 19 cases presented with neuromotor abnormality. USG was abnormal in 14 cases. RI of MCA and ACA in subjects with abnormal neuromotor outcome were 0.57 and 0.53 respectively. There was significant association between abnormal USG and decreasing RI with increasing neuromotor scale. Both ACA RI and MCA, RI were significant predictors for neuromotor impairment by univariate and multivariate logistic regression and USG was significant in univariate logistic regression. Conclusion: Abnormality detected by cranial USG and RI of cerebral vessels within few days of life in cases of perinatal asphyxia and HIE were significantly associated with poor neuromotor outcome. The strength of association in predicting neuromotor outcome was more marked with RI than USG.